A Study on The Moisture Availability and Other Conditions of Unstabilised Dunes in The Context of Present Land Use and The Future Prospects of Diversification - Mann, H S; Lahiri, A N; Pareek, O p (Annals of Arid Zone, 2016)
The prospects of plant production on desert dunes have been considered with special reference to prevailing soil plant-environment conditions. The soil moisture status of unstabilised dunes is consistently more than the stabilised ones where vegetation exists, although the moisture conditions of unstabtlised dunes, as such, may vary from one place to other depending on rainfall and other variations. High rate of water use by the dune vegetation, which is linked with the decrease in their leaf temperature, seems to be the main cause of low soil moisture status of stabilised dunes. Observations on soil temperature during the hottest period of summer days indicated a sharp fall upto about 20 cm depth from surface and at lower depths temperature variations were minimum. The conserved moisture in barren dunes, however, is not sufficient to meet the total water need of a rabi or a kharif crop although soil fertility may not be a serious limitation. The resource of conserved moisture of unstabilised dunes is being profitably utilised by certain farmers in Bikaner area, who sow water melon and long melon in March and make use of this moisture for early growth of plants while natural precipitation meets the needs of later developmental stages, The details of this unirrigated farming on barren dunes have been described with special references to cultural practice, plant growth behaviour, rate of transpiration and chemical composition of plants. The prospects of diversification of such agricultural practice have been considered where a need for developing a suitable cropping pattern, in association of grasses and trees, has been felt which may fetch maximum returns with minimum af erosion,